The Effect of Local Wisdom-Based Health Education and Mentoring on Changes in Knowledge about Nutrition for Pregnant Women at the Wara Selatan Community Health Center in 2026 - Lina Fitriani; Yenni Yenni; Arnianti Arnianti; Sry Wahyuni; Rosita Rosita (International Journal Of Health Science, 2026)
Background: Knowledge of pregnant women about nutrition is an important factor that influences the behavior of meeting nutritional needs during pregnancy. Low knowledge can increase the risk of chronic energy deficiency (CED), anemia, low birth weight (LBW), and stunting. One effort that can be done to improve the knowledge of pregnant women is through mentoring and health education based on local wisdom that utilizes the potential of local culture and food so that it is more easily accepted by the community. Objective: This study aims to analyze the effect of mentoring and health education based on local wisdom on changes in knowledge about nutrition of pregnant women at the Wara Selatan Community Health Center, Palopo City in 2026. Method: This study used a quasi-experimental design with a one group pretest-posttest design approach. The study was conducted at the Wara Selatan Community Health Center, Palopo City in May–June 2026. The study population was all 44 pregnant women who visited the Wara Selatan Community Health Center. The sample was determined using a total sampling technique so that 44 respondents were obtained. Data collection was carried out using a questionnaire on knowledge about nutrition of pregnant women before and after the intervention. Data analysis used the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Results: Before the intervention, the majority of respondents had poor knowledge (47.7%), while after the intervention, the majority were in the sufficient (45.4%) and good (43.2%) categories. The Wilcoxon Signed Rank Test results showed a Z value of -5.014 with Asymp. Sig. (2-tailed) = 0.000 (p<0.05), indicating a significant difference in knowledge before and after the intervention. Conclusion: Local wisdom-based health education and mentoring significantly improved nutritional knowledge among pregnant women at the Wara Selatan Community Health Center in Palopo City. This intervention model can be used as an innovation in antenatal care to improve the knowledge of pregnant women and support efforts to prevent CED, anemia, low birth weight (LBW), and stunting during the first 1,000 days of life.